Sagittal deformity of Garden type I and II geriatric femoral neck fractures is frequently misclassified by lateral radiographs - Madeline S. Tiee, MD, MS; Andrew G. Golz, MD; Andrew Kim, BA; Joseph B. Cohen, MD; Hobie D. Summers, MD; Anup J. Alexander, MD; William D. Lack, MD (OTA International, 2023)
Objectives:. The objective of this study was to determine the validity and inter-rater reliability of radiographic assessment of sagittal deformity of femoral neck fractures. Design:. This is a retrospective cohort study. Setting:. Level 1 trauma center. Patients/Participants:. Thirty-one patients 65 years or older who sustained low-energy, Garden type I/II femoral neck fractures imaged with biplanar radiographs and either computed tomography or magnetic resonance imaging were included. Main Outcome Measurements:. Preoperative sagittal tilt was measured on lateral radiographs and compared with the tilt identified on advanced imaging. Fractures were defined as “high-risk” if posterior tilt was ≥20 degrees or anterior tilt was >10 degrees. Results:. Of 31 Garden type I/II femoral neck fractures, advanced imaging identified 10 high-risk fractures including 8 (25.8%) with posterior tilt ≥20 degrees and 2 (6.5%) with anterior tilt >10 degrees. Overall, there was no significant difference between sagittal tilt measured using lateral radiographs and advanced imaging (P = 0.84), and the 3 raters had good agreement between their measurements of sagittal tilt on lateral radiographs (interclass correlation coefficient 0.79, 95% confidence interval [0.65, 0.88], P < 0.01). However, for high-risk fractures, radiographic measurements from lateral radiographs alone resulted in greater variability and underestimation of tilt by 5.2 degrees (95% confidence interval [−18.68, 8.28]) when compared with computed tomography/magnetic resonance imaging. Owing to this underestimation of sagittal tilt, the raters misclassified high-risk fractures as “low-risk” in most cases (averaging 6.3 of 10, 63%, range 6 − 7) when using lateral radiographs while low-risk fractures were rarely misclassified as high-risk (averaging 1.7 of 21, 7.9%, range 1 − 3, P = 0.01). Conclusions:. Lateral radiographs frequently lead surgeons to misclassify high-risk sagittal tilt of low-energy femoral neck fractures as low-risk. Further research is necessary to improve the assessment of sagittal plane deformity for these injuries. Level of Evidence:. Level IV diagnostic study.